Transmission bandwidth efficiency enhancement techniques - Shah, Asadullah; Shaikh, Asadullah (IIUM Press, 2011)
All communication channels transmit infonnation fonn one user to another using channel bandwidth mostly measured in bits/second. With the advent of latest technological tools, the bandwidth efficiency of all the channels may be enhanced beyond their normal transmission capability; mean more bits can be transmitted through the same channel. Techniques such as low bit rate encoding, variable bit rates, compression of source data, digital speech interpolation, discontinuous transmission and lost frame reconstruction are some of those signal processing techniques that can be exploited to enhance bandwidth efficiencies of the channels. In this chapter bandwidth efficiency techniques are detailed